2010
DOI: 10.1177/1078390310370476
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Postpartum Depression and Vitamin D

Abstract: Future rigorous studies investigating vitamin D and postpartum depression are warranted with larger sample sizes using confirmatory methods to diagnose postpartum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 23 publications
2
75
1
Order By: Relevance
“…The prevalence of vitamin D deficiency (82.6%) in our study was in the range of a recent study done in a sample of pregnant women at the Medical University of South Carolina in Charleston, SC, USA, which reported that 82% of women had insufficiency and/or deficiency. 24 The mean 25[OH]D levels in pregnant African-American, Hispanic and White women were 15.5 AE 7.2, 24.1 AE 8.7 and 29.0 AE 8.5 ng/ml, respectively. 31 The median serum level of 25[OH]D in our sample was 13.8 (IQR 9.4-17.1) ng/ml.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The prevalence of vitamin D deficiency (82.6%) in our study was in the range of a recent study done in a sample of pregnant women at the Medical University of South Carolina in Charleston, SC, USA, which reported that 82% of women had insufficiency and/or deficiency. 24 The mean 25[OH]D levels in pregnant African-American, Hispanic and White women were 15.5 AE 7.2, 24.1 AE 8.7 and 29.0 AE 8.5 ng/ml, respectively. 31 The median serum level of 25[OH]D in our sample was 13.8 (IQR 9.4-17.1) ng/ml.…”
Section: Resultsmentioning
confidence: 92%
“…21,22 Recent findings from a randomised trial suggested that high doses of supplemental vitamin D may improve mild symptoms of depression. 23 In addition, several studies have found that mood disorders are significantly associated with low levels of serum 25[OH]D, a reliable measurement of vitamin D. 24 There is little research in the literature exploring the implications of decreased levels of 25[OH]D on the prevalence of PPD. Therefore, the purpose of the present study was to assess a possible relationship between vitamin D status and PPD using the serum level of 25[OH]D collected 24-48 hours after delivery in a Chinese cohort sample.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers explored the relationship between low vitamin D and pregnancy-related depression. Murphy et al showed a link between maternal low serum concentrations of 25-hydroxyvitamin D and elevated depression scores after birth (16). In a study by Brandenburg et al, a reverse link was found between 25-hydroxyvitamin D concentration and maternal depression score at 16 weeks of gestation (17).…”
Section: Introductionmentioning
confidence: 90%
“…In a study done to shed a light on the effect of vitamin D deficiency on the occurrence of PPD, a significant correlation between low levels of 25-OH D3 over time, which is a sign of postpartum depression, and high EPDS scores was discovered. 24 Postpartum depression was most often seen in winter months. 27,28 In a study, Fu et al have found serum 25-OH D3 levels in women without PPD higher that in women suffering from postpartum depression.…”
Section: Omega-3 Fatty Acidmentioning
confidence: 99%
“…23 Vitamin D deficiency (25-OH D3 <32 ng/mL) is an epidemic affecting 75% of women of childbearing age. 24 Maternal vitamin D deficiency is common during pregnancy and even with vitamin D supplements vitamin D is sufficient in only a small percentage of women and babies. 25 Low levels of vitamin D can be overlooked as a risk factor for PPD.…”
Section: Omega-3 Fatty Acidmentioning
confidence: 99%